Epidemiological characteristics of COVID-19 inpatient deaths during the first and second waves in Limpopo Province, South Africa - Tshitangano, Takalani G.; Setati, Musa E.; Mphekgwana, Peter M.; Ramalivhana, Naledzani J.; Matlala, Sogo F. (MDPI, 2022)
Abstract: More COVID-19 inpatient deaths occurred during the second wave when compared to the first wave in South Africa in both the public and private sectors. This study describes the characteristics of 969 COVID-19 inpatient deaths in the public sector of Limpopo Province during the first and second waves using population-based retrospective design. The results indicate that about 84% of deaths were aged 50+ years; 53.6% were females; 43% occurred in Capricorn district; 56% occurred in PUI wards; 64% had hypertension followed by diabetes mellitus; 88% manifested with shortness of breaths/respiratory distress on admission. The study concludes that as the average age among the population aged 60+ was greater among females than males, the increased death among females compared to males might be influenced by the older age of female inpatients during the first and second waves in Limpopo Province. Some COVID-19 inpatient deaths are possibly preventable if older women may be taken into consideration when planning prevention and management interventions in future pandemics.
Journal article published in The Journal of Respiration 2022, 2, 111–122
Keywords: COVID-19; Inpatient; Case fatalities; Limpopo province; South Africa; COVID-19 (Disease); COVID-19 Pandemic, 2020-; Epidemiology -- Research; COVID-19 Pandemic, 2020- -- South Africa -- Limpopo